The Psychometric Characteristics Of Cornell Critical Thinking Test Level (x) On A Sample Of Talented Students "A Field Study In The National Centre For The Distinguished In Syria" - Boubou, Mounzer; Chrebah, Bouchra; Shbeeb, Hanaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed to investigating the prevalence of Cornell Critical Thinking Test Level (x) on a sample of talented students in the national Centre for the distinguished (NCD) in Syria, and to identify the levels of critical thinking among talented students, and whether these differed according to (students’ gender, academic level), the sample consisted of (167) talented students, the results showed that the participants exhibited an average level of Critical Thinking, and no Significant differences were found due to gender, the results also revealed that Significant differences were found due to academic level for the third academic level.